Estimation of salivary calcium level as a screening tool for the osteoporosis in the post-menopausal women: A prospective study - Amit Wasti; Jyoti Wasti; Ritunja Singh (Wolters Kluwer Medknow Publications, 2020)
Aims and Objectives: The aim and objective of the present study was to explore the use of salivary calcium levels as a diagnostic biochemical marker for osteoporosis in menopausal women and also to find the correlation among oestrogen level, bone density and salivary calcium level. Materials and Methods: The study included 180 individuals and they were divided into three groups with 60 individuals in each group, comprised of healthy women, pregnant women and post-menopausal women. All the women were asked to collect at least 2 ml of unstimulated whole saliva in the sterile plastic sample containers. The samples were immediately subjected to biochemical estimation of calcium. Similarly, estimation was done for oestrogen level and bone density among all the groups. The results were obtained by one-way analysis of variance (ANOVA) using Statistical Software SPSS version 17. For the correlation among the bone density, salivary calcium level and serum oestrogen levels, Pearson's correlation was used. Results: The mean salivary calcium level in the healthy women group was found to be 3.0 ± 0.50 μg/ml. Similarly, pregnant women and post-menopausal group, it was found to be 3.20 ± 0.72 and 7.5 ± 0.90 μg/ml, respectively. When the intergroup comparison was done in the three groups, it was found to be highly significant (P = 0.001). Similarly, the difference in mean value for oestrogen level and bone density was highly significant among all the groups (P = 0.001). Conclusion: Among all the three groups, the salivary calcium levels do exhibit the correlation with bone mineral density. In the post-menopausal group, there was significant increase in salivary calcium level compared to other groups. Similarly, the study showed a negative correlation between salivary calcium and serum oestrogen. This substantiates the point that salivary calcium levels can definitely indicate the possibility of the presence or absence of osteoporosis in post-menopausal women.